Aktivitas Antidermatofitik Ekstrak Daun Urang-aring (Eclipta alba (L.) Hassk) terhadap Trichophyton mentagrophytes - Ikawati, Hartanti Dian (Jurnal Kefarmasian Indonesia, 2014)
Emergence of drug resistance in a fungal infection therapy had driven the need for a search of a new therapeutic agent. Traditional approach is now being marked by most people to combat this resistance problem. Plants can acts as a source of antimicrobial agents. Eclipta alba,L. Hassk leaves has been traditionally used to cure skin illnesses caused by fungal infection. The aim of this study is to analyze the antidermatophytic activity of Eclipta alba, L. Hassk leaves extract against Trichophyton mentagrophytes. Eclipta alba (L.) Hassk leaves were extracted gradually with hexane, ethyl acetate, ethanol and water. A serial concentration 0 mg/ml, 12,5 mg/ml, 25 mg/ml, 50 mg/ml and 100 mg/ml of those four fraction was made subsequently. The antidermatophytic activity was done by gel diffusion method. Zone of inhibition was measured and analyzed with ANOVA continued with DMRT (Duncan Multiple Range Test). The antifungal test showed that hexane, ethyl acetate and ethanolic extract of Eclipta alba, L. Hassk leaves were effective to inhibit the growth of Trichophyton mentagrophytes but not significantly different (p≥0,05). Water extract showed no inhibition on Trichophyton mentagrophytes